Exposure to microbial contaminants in metalworking fluids (MWF) and the fractional exhaled nitric oxide (FeNO) levels among machining industry workers - Hashim, Nurul Maizura; Hashim, Zailina; Awang Hamat, Rukman; Kadir @ Shahar, Hayati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Water based Metalworking fluids (MWF) are commonly used in machining industries and are excellent media for microorganism growth. The study aimed at determining the relationship between the airway inflammation as indicated by fractional exhaled nitric oxide (FeNO) with the microbial contaminants of MWF in aerosol and bulk sample as well as the workers’ reported respiratory health symptoms. Methods: This cross sectional study was carried out on 138 machining workers. Their FeNO were measured using NIOX-MINO instrumentation. The microbial assessments of bacteria and fungus were carried out on the MWF bulk samples and the aerosol using a sampler DUO SAS SUPER 360TM. Results: Findings showed significant difference in the FeNO levels in workers from various job sections (p=0.01). Significant relationships found between high FeNO levels with their closeness to the machines (p=0.03), high number of machines in the workplaces (p=0.02), high environmental bacteria colonies (p=0.04), longer employment years (p<0.001) and more frequent cough reported (p=0.03). Conclusion: Risk factors in the work-place which contributed to higher airway inflammation include their short distance and high number of machines, high environmental bacteria colonies in aerosol and bulk samples as well as longer employment years. Exposures to MWF had also resulted in significantly increased coughing among the respondents.